Heat pipes in battery thermal management systems for electric vehicles: A critical review. (25th January 2023) - Bernagozzi, Marco; Georgoulas, Anastasios; Miché, Nicolas; Marengo, Marco
Highlights: EV current situation analysed and needs for Thermal management highlighted. Reviewed more than 100 papers on the application of Heat Pipes to BTMS. Papers classified depending on the additional cooling method that complemented Heat Pipes. Identified research limitations and next steps to improve adoption of this technology by EV market. Abstract: Electric Vehicles (EVs) are at the centre of the recent industrial sustainable revolution and are identified as a potential route to reduce GHG emissions and tackling global warming. In the development of EVs, battery thermal management is a crucial aspect in ensuring high performance, market competitiveness and environmental sustainability. It is well known how high or low operating temperatures give negative effects on battery performance and operative life. Improving on the existing Battery Thermal Management Systems (BTMS) technologies would lead to an overall improvement of the vehicles, from the operator/costumer point of view, in terms of all-electric range and performance, charging time and cost. Only two BTMS technologies are employed at the moment, in commercial vehicles, which are air and liquid cooling. This review aims to extend on current knowledge on potential technologies applicable to BTMS, providing a thorough analysis of the research done on particular type of passive thermal devices, known as Heat Pipes, utilized as BTMS, articulating the analysis on the different types of Heat Pipes and the methods used to remove the excess heat at their condensers. The purpose of this review is to collect the results of different investigations, highlighting strengths and flaws, and ultimately collecting the following next steps that Heat Pipe BTMS research should pursue: focus on ambient temperature effect, foresee system scalability to battery modules and employ environmentally friendly working fluids.